Endotracheal Tube Electrodes to Assess Vocal Cord Motor Function During Surgery in the Cerebellopontine Angle. Issue 3 (22nd June 2015) - Romagna, Alexander; Rachinger, Walter; Schwartz, Christoph; Mehrkens, Jan-Hinnerk; Betz, Christian; Briegel, Josef; Schnell, Oliver; Tonn, Jörg-Christian; Schichor, Christian; Thon, Niklas
Abstract: BACKGROUND: The 10th cranial nerve (CN X) is at risk during surgery in the lower cerebellopontine angle (CPA). OBJECTIVE: To evaluate endotracheal surface electrodes for assessment of CN X motor function during CPA surgery. METHODS: Twenty patients were enrolled. Electrophysiological recordings were analyzed and retrospectively correlated with clinical, imaging, and intraoperative data. RESULTS: Recordings from endotracheal surface electrodes were reliable and eligible for analyses in 17 patients; in 3 patients, no surface electrode compound motor action potentials (CMAPs) could be obtained. Those patients with sufficient recordings underwent surgery in the CPA for tumors in 14 patients and for nontumor pathologies in 3 patients. In 12 patients, bipolar stimulation of motor rootlets in the CPA resulted in simultaneous CMAPs recorded from both surface electrodes and needle electrodes placed in the soft palate. Coactivation was particularly seen in patients with an intricate relationship between lower cranial nerves and tumor formations (n = 9/10). Amplitudes and latencies of vocal cord CMAPs showed high interindividual but low intraindividual variability. Parameters were not well correlated with the type of surgery (tumor vs nontumor surgery) and lower CN anatomy (displaced vs undisplaced). In 2 patients, vocal cord CMAPs were lost during tumor surgery, which was associated with postoperative dysphagia and hoarseness in 1 patient. CONCLUSION: Endotracheal surface electrodes allow identification of vocal cord motor rootlets in the CPA. Worsening of CMAP parameters might indicate functional impairment. These aspects support the use of endotracheal surface electrodes in selected patients in whom the vagus nerve might be at risk during CPA surgery.